Isolasi Dan Identifikasi Bakteri di Lingkungan Laboratorium Mikrobiologi Klinik RSUDZA Banda Aceh - Amiril Arifin; Zinatul Hayati; Kurnia Fitri Jamil (Jurnal Ilmiah Mahasiswa Kedokteran Komunitas, 2016)
One of the roles of Clinical Microbiology Laboratory is a supporting-investigation data provider about bacterial patogens that may cause infection disease to the patients. Hence, it’s accuracy is considered necessary. Living Bacteria in the Clinical Microbiology Laboratory environment is one source of the contaminants to clinical sample, therefore misidentification can occur. Research objectives were to isolate and identificatebacteriain the Clinical Microbiology Laboratory environment, RSUDZA Banda Aceh, and to determine its source. The research type was laboratory observations. The research samples were surfaces such as tables, wall, floor, Biosafety Cabinet (BSC), incubator, handle of door and refrigerator, computer keyboard, laboratory staffs’ nasal mucosa and unwashed palm. Thirty four isolates were obtained from 25 samples. The identification result showed Gram positive rods bacteria, Pantoea spp, Acinetobacter baumannii, Staphylococcus warneri, Staphylococcus haemolyticus, Staph. hominis spp hominis, Staphylococcus aureus, Staphylococcus epidermidis, Leuconostoc pseudomesenteroides, Citrobacter koseri, Burkholderia cepacia, Sphingomonas paucimobilis, Lactococcus garvieae, and Staphylococcus gallinarum